Issuance of Health Certificate (HC) and Health Fish Fishery Products (Ki-D1) on Seawater Lobster Panulirius Sp at BBKIPM Makassar - Samsidar; Budi Setia Nusa; Asrifan, Andi (MultiTech Publisher, 2023)
Lobster is a marine animal that belongs to the Crustacean or shrimp, this type of giant shrimp belongs to the Nephropidae and also the Homaridae family. The advantages of lobster as an export product, namely increasing the country's foreign exchange. The requirements for export eligibility are that lobsters are not in a state of laying eggs that are visible on the outer abdomen and carapace size of 6 cm and weight above 150 grams/lobster. The method of activity implementation is carried out through field work activities, literature studies and interviews with primary and secondary data. interviews with primary and secondary data types. BBKIPM Makassar conducts several procedures that must be fulfilled by the applicant, namely submission of applications, document examination, physical examination of lobsters Panulirius sp and clinical examination of carrier media, the process of issuing health certificates (HC), and KI-D1. (HC) and KI-D1, verification and payment of PNBP and supervision. After all procedures are fulfilled, the product can proceed to the exporting.